Education and development of children with autism spectrum disorders - Marchuk, L. S. (ТОВ "Поліграфцентр "Ліра", 2022)
I raise this topic for professionals who work with children with autism spectrum disorders(ASD), so that it is possible to work with the «native » defi cits of autism and see changes and progress in areas in which most do not even hope to receive this progress.And also for parents whohave children with ASD, so that they can change the style of their daily interaction with the child and open new opportunities for development and progress. That is, it will be interesting for everyone who interacts with children with ASD, so that you can learn what abilities need to be developed so that the child can reach the level of an independent and happy life.
Keywords: еducation; development; children; autism spectrum disorders